2013
DOI: 10.5120/11588-6926
|View full text |Cite
|
Sign up to set email alerts
|

Correlation based Fingerprint Image Segmentation

Abstract: In this paper, a correlation based fingerprint image segmentation technique is presented. Segmented is a useful image processing tool generally used in Machine vision applications in the Pattern Recognition and classification that leads to the separation of area of interest (AOI) from an image based on some image parameters like gray levels. In this proposed method, direction based segmentation is presented without computing and use of any directional field whose effectiveness has been evaluated for several fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The inferred highlights, which are tabulated in Table 1, gives a wide distinction between the typical and malignant growth pictures and the proposed pressure calculations don't influence the qualities much. The ideal calculation is picked dependent on the arrangement accuracy [21,22]. The GLCM features are analysed in this work, so as to characterize the lung CT images.…”
Section: Resultsmentioning
confidence: 99%
“…The inferred highlights, which are tabulated in Table 1, gives a wide distinction between the typical and malignant growth pictures and the proposed pressure calculations don't influence the qualities much. The ideal calculation is picked dependent on the arrangement accuracy [21,22]. The GLCM features are analysed in this work, so as to characterize the lung CT images.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for each block, the average and coherence data is computed in order to divide the image into two regions by using K-means clustering approach. The correlation based fingerprint image segmentation is used in [16]. Fahmy, et al [17] proposed a technique that utilizes morphological processing to extract the foreground from the fingerprint image.…”
Section: Related Workmentioning
confidence: 99%
“…Characteristics such as gradient cohrence and ridge direction can be classified into gradient based characteristics. The gradient coherence and ridge direction features are calculated by (16) and (20) respectively.…”
Section: B Gradient Based Characteristicsmentioning
confidence: 99%
“…In Yang, et al [14][15] a novel algorithm of segmentation of fingerprint images was subjected using an unsupervised method of learning based on K-means classification.Thus, average and consistency data are calculated for each block to divide the image into two regions using the clustering approach of K-means. The segmentation of the correlation-based fingerprint image is used in [16].Fahmy, et al [17] suggested a technique using morphological processing to remove the foreground from the fingerprint image. After dividing the image into nonoverlapping blocks, this technique used the feature vector for each block to perform segmentation of fingerprints.The adaptive thresholding is then used to transform the image of the fingerprint to binary.…”
Section: Related Workmentioning
confidence: 99%
“…The gradient is used to obtain the directional variation of the intensity value along with an image I mg direction of size x Xy. Characteristics like gradient coherence and direction of the ridge can be classified into characteristics based on gradient.The coherence of the gradient and the direction of the ridge are calculated respectively by (16) and (20).…”
Section: Gradient-based Characteristicsmentioning
confidence: 99%